Perceptions and opinions of Canadian pet owners about anaesthesia, pain and surgery in small animals. (8th April 2017) - Steagall, P. V.; Monteiro, B. P.; Ruel, H. L. M.; Beauchamp, G.; Luca, G.; Berry, J.; Little, S.; Stiles, E.; Hamilton, S.; Pang, D.
Abstract : Objectives: The aim of this study was to evaluate the perceptions and opinions of Canadian pet owners about anaesthesia, pain and surgery in dogs and cats. Methods: Six Canadian veterinary hospitals participated. Each practice received 200 copies of a questionnaire that were distributed to pet owners. Questions regarding the use of analgesics, anaesthesia, surgery and onychectomy (cats) were included. Responses were transformed into ordinal scores and analysed with a Cochran‐Mantel‐Haenszel test. Results: A total of 849 out of 1200 questionnaires were returned. Owners believed more frequently that analgesics are needed for surgical procedures than for the medical conditions. Owners rated as very important/important: "knowing what to expect during illness/injury/surgery" (99·3%), "being assured that all necessary analgesic drugs/techniques will be used" (98·6%), "being informed about procedures/risk" (98·5%), and having a board‐certified anaesthesiologist (90·5%). Most owners agreed/partly agreed that pain impacts quality of life (94·2%), and affects their pet's behaviour (89·5%). Most respondents (69%) were women; they were significantly more concerned than men about anaesthesia, pain, cost and client‐communication. Cat owners believed that analgesics were necessary for some procedures/conditions significantly more often than canine‐only owners. Pet owners with previous surgery disagreed more frequently that "pain after surgery can be helpful" and that "pain in animals is easy to recognize" than those without previous surgery. Most owners think onychectomy should be banned in cats (56·4%). Clinical Significance: This study identified important areas of client communication regarding pain and its control in pets.